Uji Validitas dan Reliabilitas Konstruk Skala Spirit at Work dalam Konteks Tenaga Pendidik - Arung Samudera; Adinda Nayla Syifa Hardani; Devi Nurlita (Jurnal Riset Psikologi, 2026)
Abstract. Long-distance romantic relationships involve physical separation that can trigger separation anxiety. This study aimed to examine the extent to which the three dimensions of attachment (i.e., trust, communication, and alienation) predicted symptoms of separation anxiety among young adults in long-distance romantic relationships. Participants were 110 young adults aged 18–25 who were in long-distance romantic relationships. Attachment was measured using the parent scale of the Inventory of Parent and Peer Attachment (IPPA), while separation anxiety symptoms were measured using the Adult Separation Anxiety Questionnaire (ASA-27). The results revealed that alienation explained 62% of the variance in separation anxiety symptoms and was a strong, significant predictor of separation anxiety symptoms among young adults in long-distance romantic relationships. The findings of this study have implications for the development of interventions focused on targeting emotional alienation stemming from early attachment experiences with parents, which affect individuals in long-distance relationships. Abstrak. Hubungan romantis jarak jauh melibatkan perpisahan fisik yang dapat memicu kecemasan berpisah. Penelitian ini bertujuan untuk menyelidiki sejauh mana tiga dimensi kelekatan (kepercayaan, komunikasi, dan alienasi) memprediksi gejala kecemasan berpisah pada orang dewasa muda yang menjalani hubungan jarak jauh. Partisipan penelitian adalah 110 orang dewasa muda berusia 18-25 tahun yang sedang menjalani hubungan romantis jarak jauh. Kelekatan diukur menggunakan skala orang tua dari Inventory of Parent and Peer Attachment (IPPA), sedangkan gejala kecemasan berpisah diukur menggunakan Adult Separation Anxiety (ASA-27). Hasil analisis menunjukkan bahwa alienasi menjelaskan 62% varians gejala kecemasan berpisah dan merupakan prediktor yang kuat dan signifikan terhadap gejala kecemasan berpisah pada dewasa muda yang menjalani hubungan romantis jarak jauh. Hasil penelitian ini memiliki implikasi terhadap pengembangan intervensi yang berfokus pada penanganan alienasi emosional yang berasal dari pengalaman kelekatan awal dengan orang tua yang berdampak pada individu dalam menjalani hubungan romantis jarak jauh.